1997
DOI: 10.1002/(sici)1097-4598(199707)20:7<809::aid-mus4>3.0.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic evaluation by means of standard tests and power spectral analysis in multiple sclerosis

Abstract: Standard autonomic tests [heart rate response to deep breathing (HRDB), change in systolic blood pressure due to tilt], and spectral analysis of heart rate (HR), arterial blood pressure (ABP), and the associated transfer function analysis (gains and phases) were performed in 20 patients with multiple sclerosis to determine their diagnostic value. Transfer function analysis suggested impairment of baroreflex function in 7 patients and an alteration of cardiorespiratory coupling on a brain stem level in 4 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
2

Year Published

1998
1998
2011
2011

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 26 publications
0
8
0
2
Order By: Relevance
“…The impairment in parasympathetic function is supported by studies in which spectral analysis and 24-hour heart rate variabilities showed significantly smaller oscillations in high frequency (function of parasympathetic cardiovagal activity) in MS patients compared to healthy controls [13,16,17]. Ferini-Strambi et al evaluated autonomic function in sleep and showed that the ratio of the mean RR-interval before body movement during sleep to mean RR-interval during wakefulness (RRs/w), an index of vagal activity, was impaired in MS patients [12].…”
Section: Discussionmentioning
confidence: 91%
“…The impairment in parasympathetic function is supported by studies in which spectral analysis and 24-hour heart rate variabilities showed significantly smaller oscillations in high frequency (function of parasympathetic cardiovagal activity) in MS patients compared to healthy controls [13,16,17]. Ferini-Strambi et al evaluated autonomic function in sleep and showed that the ratio of the mean RR-interval before body movement during sleep to mean RR-interval during wakefulness (RRs/w), an index of vagal activity, was impaired in MS patients [12].…”
Section: Discussionmentioning
confidence: 91%
“…A number of investigations have focused on cardiovascular reflex tests [2,11,12,16,17,23,24,26,36,38], but these have provided conflicting data about the frequency and distribution of cardiovascular autonomic dysfunction in MS. More than 50% of the patients observed by Pentland et al [26], Nordenbo et al [24], Gallai et al [12], and Anema et al [2] showed abnormal responses on one or more tests, while much lower frequencies were found by Linden et al [16,17], Ferini-Strambi et al [8], Frontoni et al [11] and Nasseri et al [23]. The proportion of patients with two or more abnormal test results (which is generally taken to establish significant autonomic dysfunction [21]) ranged from 10% [38] to 50% [34].…”
Section: Cardiovascular Reflex Testsmentioning
confidence: 99%
“…Other manifestations of autonomic dysfunction may include sweating, gastrointestinal, and cardiovascular disturbances. In this regard, orthostatic dizziness (OD) has been found in up to 49% of patients [2,16,38], and abnormal responses to cardiovascular reflex tests are reported with varying frequencies [2,11,12,17,24,26,36,38]. However, the mechanisms leading to OD are poorly understood, and the correlation with autonomic function tests (AT) has not been systematically studied before.…”
mentioning
confidence: 99%
“…L'hypotension toucherait près de 50 % des patients atteints de SEP [20]. La dysrégulation cardiovasculaire au cours de la SEP est bien mise en évidence par l'étude de la variabilité de la FC [2,21,22]. L'atteinte pupillaire est décrite avec une [23].…”
Section: Discussionunclassified